Examining the Impacts of Grid Tariff on the Economic Viability of Photovoltaic Energy: The Case of Residential Power Generation in Brazil - Branco, José Eduardo Holler; Junior, Paulo Nocera Alves; Okamura, Fernando; Melo, Isotilia Costa (International Journal of Energy Economics and Policy, 2024)
On-grid photovoltaic systems (PVs) hold immense potential as source of renewable energy, particularly in nations with abundant solar irradiation and large territories. Brazil, in particular, has emerged as a noteworthy example, driving an annual PV capacity installation rate above 150% since 2013. However, the recent Normative Resolution 1.059/2023, stablished by the National Electricity Energy Agency, has introduced grid tariff for utilizing grid infrastructure in Brazil. In light of this, our study aims to assess the impacts of this policy on the economic feasibility of medium-sized residential PVs (rooftops). Our finds demonstrated that the financial indicators for investing in on-grid PVs within medium-sized family homes in Brazil were very attractive prior to 2023, with an average Internal Return Rate (IRR) of 22.7% and a payback of 5.0 years. However, as consequence of the new policy these indicators will deteriorate and reach an average IRR of 15.7% and an average payback of 7.2 years, progressively until 2030. Additionally, it will increase almost 50% the PV electricity levelized cost. We recommend further research directions for policymakers and researchers encompassing several strategies for encouraging again the PV energy in the country, such as promoting joint procurement initiatives, and implementing subsidies for reducing photovoltaic system prices.